De novo assembly of the carrot transcriptome from short-read sequences identifies novel genes and reveals genetic diversity - Iorizzo, Massimo (2011)
Background: Among next generation sequence technologies, platforms such as Illumina and SOLiD produce short reads but with higher coverage and lower cost per sequenced nucleotide than 454 or Sanger. A challenge now is to develop efficient strategies to use short-read length platforms for de novo assembly and marker development. The scope of this study was to develop a de novo assembly of carrot ESTs from multiple genotypes using the Illumina platform, and to identify polymorphisms. Results: A de novo assembly of transcriptome sequence from four genetic backgrounds produced 58,751 contigs and singletons. Over 50% of these assembled sequences were annotated allowing detection of transposable elements and new carrot anthocyanin genes. Presence of multiple genetic backgrounds in our assembly allowed the identification of 114 computationally polymorphic SSRs, and 20,058 SNPs at a depth of coverage of 20× or more. Polymorphisms were predominantly between inbred lines except for the cultivated x wild RIL pool which had high intra-sample polymorphism. About 90% and 88% of tested SSR and SNP primers amplified a product, of which 70% and 46%, respectively, were of the expected size. Out of verified SSR and SNP markers 84% and 82% were polymorphic. About 25% of SNPs genotyped were polymorphic in two diverse mapping populations. Conclusions: This study confirmed the potential of short read platforms for de novo EST assembly and identification of genetic polymorphisms in carrot.